IMPROVEMENT OF SULFUR-BASED CONCRETES UNDER THE INFLUENCE OF TEMPERATURE - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; F.Dadaxanov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. The theoretical basis of sulfur concrete was studied in the article. A number of positive properties of sulfur concrete were studied, and the results of practical work on improving the fire resistance properties were studied.